Mathematics competency and situational mathematics anxiety: What are the links and how do these links affect teacher education programs? - Cooke, Audrey; Hurst, Chris (Australian Association for Research in Education (AARE), 2012)
The issue of mathematics anxiety and its possible links to mathematical competence have long been of concern to mathematics educators, particularly with the potential of the effects of mathematics anxiety to be transmitted from teacher to student. Hence it is in the interests of teacher educators to understand the nature of mathematics anxiety and connections that may exist between mathematics anxiety and mathematical competence. This study examines the connections between sitting a mathematics competency test and situational anxiety in a group of 47 pre-service teachers in their first year of study. Data were analysed by grouping the pre-service teachers into one of three groups based on their passing test score (a mark of 80 – 89% or a mark of 90% and above) or their having not sat the competency test. Results indicate that there were strong correlations between the three groups of pre-service teachers in their overall responses to the anxiety questionnaires. However, when data were considered in terms of situations (working in a group, taking a test, and teaching mathematics) and domains (somatic, knowledge, cognitive, and attitude), differences were evident. The implications of these results and the potential impact on teacher education programs are discussed.